Glutamine antagonists for the treatment of cognitive deficits - NEDELCOVYCH MIKE; SLUSHER BARBARA; HOLLINGER KRISTEN; VOLSKY DAVID (2018)
The presently disclosed subject matter relates to methods, uses, and pharmaceutical compositions comprising at least one glutamine antagonist, or a prodrug or analog thereof, for the treatment of cognitive deficits, such as those associated with neurological or neurodegenerative disorders, psychiatric or mood disorders, and HIV-associated neurocognitive disorders (HAND)). The presently disclosed subject matter provides supporting PK and biomarker data. These data predict the use of glutamine antagonists (or their prodrugs or analogs) for the treatment of cognitive deficits in general, and specifically for cognitive deficits associated with neurological or neurodegenerative disorders, psychiatric or mood disorders, and HAND. 本发明公开的主题涉及用于治疗认知缺陷的方法、用途和药物组合物，所述药物组合物包含至少种谷氨酰胺拮抗剂或其前药或类似物，所述认知缺陷例如与神经障碍或神经退行性疾病、精神障碍或情绪障碍以及HIV相关性神经认知障碍(HAND)相关的那些。本发明公开的主题提供了支持性PK和生物标志物数据。这些数据预测谷氨酰胺拮抗剂(或其前药或类似物)用于治疗般认知缺陷，特别是与神经障碍或神经退行性疾病、精神障碍或情绪障碍以及HAND相关的认知缺陷的用途。